MEASURING BRAND EQUITY: THE PERSPECTIVE OF STARBUCKS' CUSTOMERS - Puspaningrum, Astrid (Universitas Brawijaya, Indonesia, 2020)
This study aims to analyze brand loyalty in mediating the effect of brand association and brand awareness on brand equity. The population of this study is customers of Starbucks Coffee in Malang City, with a sample of 160 respondents. The data was analyzed using Structural Equation Modeling. The results showed that brand association and brand awareness influenced brand equity, and brand loyalty was able to mediate the effect of brand awareness and brand association on brand equity. To increase brand loyalty, which in turn leads to brand equity, the management team of Starbucks Coffee has to provide a strategy in building brand awareness and brand association. Future researchers can develop this study by adding more variables, for example, is brand trust.